2009
DOI: 10.1148/radiol.2493071999
|View full text |Cite
|
Sign up to set email alerts
|

Lumbar Spine: Reliability of MR Imaging Findings

Abstract: Purpose:To characterize the inter-and intraobserver variability of qualitative, non-disk contour degenerative findings of the lumbar spine at magnetic resonance (MR) imaging. Materials and Methods:The case accrual method used to perform this institutional review board-approved, HIPAA-compliant retrospective study was the random selection of 111 interpretable MR examination cases of subjects from the Spine Patient Outcomes Research Trial. The subjects were aged 18 -87 years (mean, 53 years Ϯ 16 [standard deviat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
123
3
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 171 publications
(138 citation statements)
references
References 26 publications
(33 reference statements)
8
123
3
3
Order By: Relevance
“…Modic changes were evaluated according to the Modic classification system: Type 1-Hypointense T1 signal and hyperintense T2 signal, Type 2-Hyperintense T1 signal and iso or slightly hyperintense T2 signal [9].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
See 1 more Smart Citation
“…Modic changes were evaluated according to the Modic classification system: Type 1-Hypointense T1 signal and hyperintense T2 signal, Type 2-Hyperintense T1 signal and iso or slightly hyperintense T2 signal [9].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…A posterior HIZ was defined as an area of high signal intensity in the posterior annulus fibrosus that was brighter than nucleus pulposus on T2-weighted images [9].…”
Section: Magnetic Resonance Imaging (Mri)mentioning
confidence: 99%
“…Gorbach et al [23] found the extent of facet joint arthropathy defined anatomically on MRI and CT was not a significant predictor for outcome in a cohort of 42 patients undergoing facet joint blocks (p=0.57-0.95). Carrino et al [25] used weighted Kappa statistics for measuring interobserver agreement between four specialist readers of MR lumbar spine for facet arthropathy in 111 scans and found inter-observer variability of 0.54 (CI 95 %, 0.50-0.57). Inconsistent interobserver variability suggests that the test does not provide an easily interpretable assessment and both MRI and CT reports can be inconclusive regarding the presence or absence of facetal arthropathy.…”
Section: Discussionmentioning
confidence: 99%
“…In the clinical practice of radiology, consensus, when interpreting the medical image, is hardly ever reached, especially with diagnostic tests where interpreted components are subjective. Several studies showed substantial observer variability not only among non-specialized radiologists during standard clinical reporting [2,3], but also at the expert level of image interpretation [4,5].…”
Section: Introductionmentioning
confidence: 99%